Detection of SGI1/PGI1 Elements and Resistance to Extended-Spectrum Cephalosporins in Proteae of Animal Origin in France - Schultz, Eliette; Cloeckaert, Axel; Doublet, Benoît; Madec, Jean-Yves; Haenni, Marisa (Frontiers in Microbiology, 2017)
Proteae, and especially Proteus mirabilis, are often the cause of urinary tract infections (UTIs) in humans. They were reported as carriers of extended-spectrum β-lactamase (ESBL) genes, and recently of carbapenemases, mostly carried by the Salmonella genomic island 1 (SGI1) and Proteus genomic island 1 (PGI1). Proteae have also lately become an increasing cause of UTIs in companion animals, but antimicrobial susceptibility data in animals are still scarce. Here, we report the characterization of 468 clinical epidemiologically unrelated Proteae strains from animals collected between 2013 and 2015 in France. Seventeen P. mirabilis strains (3.6%) were positive for SGI1/PGI1 and 18 Proteae (3.8%) were resistant to extended-spectrum cephalosporins (ESC). The 28 isolates carrying SGI1/PGI1 and/or ESC-resistance genes were isolated from cats, dogs, and horses. ESBL genes were detected in six genetically related P. mirabilis harboring blaV EB-6 on the SGI1-V variant, but also independently of the SGI1-V, in 3 P. mirabilis strains (blaVEB-6 and blaCTX-M-15) and 1 Providencia rettgeri strain (blaCTX-M-1). The AmpC resistance genes blaCMY -2 and/or blaDHA-16 were detected in 9 P. mirabilis strains. One strain presented both an ESBL and AmpC gene. Interestingly, the majority of the ESBL/AmpC resistance genes were located on the chromosome. In conclusion, multiple ESC-resistance genetic determinants are circulating in French animals, even though SGI1-V-carrying P. mirabilis seems to be mainly responsible for the spread of the ESBL gene blaVEB-6 in dogs and horses. These results are of public health relevance and show that companion animals in close contact with humans should be regarded as a potential reservoir of ESC-resistant bacteria as well as a reservoir of ESC-resistance genes that could further disseminate to human pathogens.